Prevalencia, características clínicas y socioeconómicas de teniasis y cisticercosis en una población de Lurín - 2004 - Castillo-Contreras, Ofelia (2021)
Objectve: To determine the prevalence of intestinal taeniasis and seroprevalence of cysticercosis of the fried pork seller from Lurin in Lima-Perú and to know the epidemiological, socio-economic characteristics and asociated symptoms with the parasitosis. Material and methods: We carried out a tranversal descriptive study with the fried pork seller from an urban community “Julio C. Tello” in Lurin. We get a informed assent of everybody participants. We carried out a socioepidemiological survey and we took samples of blood to detect specific antibodies to cysticerci (EITB) and of feces for the detection of coproantigenos of Taenia sp. (ELISA). All the samples were analyzed in Cysticercosis's Laboratory of the Institute National of Neurological Sciences. The protocol was approved by the Committee of Ethics of the Faculty of San Fernando's Medicine Results: Of 49 surveyed, the 89.8 % of the population was participating in the preparation of fried pork and attention to the public. 81.6% support that they always wash their hands after defecating, and 65.3 % support that they always do it before consuming food. There were 41 blood samples that were negative for cysticercosis. The detection of coproantigens of Taenia sp. they were negative in all cases. There were no eggs of Taenia sp. in the examination of microsedimentation. The places for selling the fried pork have basic services. Discussion: The sanitary conditions and hygienic suitable habits would reduce the risk of infection. The consumption of meat of pig in the shape of fried pork might not be associated with the transmission of this parasite. Conclusion: The obtained information indicates that there's no taeniasis and cysticercosis in the studied population.